Handbook of social psychology - Ward, Amanda; Delamater, John (Handbooks of Sociology and Social Research, 2013)
This handbook provides a broad overview of the field of social psychology and up-to-date coverage of current social psychological topics. It reflects the recent and substantial development of the field, both with regard to theory and empirical research. It starts out by covering major theoretical perspectives, including the interactionist, identity, social exchange, social structure and the person perspectives. Next, it discusses development and socialization in childhood, adolescence and adulthood. In addition to updated discussions of topics that were included in the first edition, the part examining personal processes includes entirely new topics, such as social psychology and the body and individual agency and social motivation. Interpersonal processes are discussed from a contemporary perspective with a focus on stress and health. The final section examines the person in sociocultural context, and includes another topic new to the second edition, the social psychology of race and gender and intersectionality.